2018
DOI: 10.1007/s00066-018-1348-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards a universal MRI atlas of the prostate and prostate zones

Abstract: The MRI atlas-based segmentation method achieved good results for prostate, PZ, and TZ compared to expert contoured volumes. Combined atlases performed similarly to matching atlas and scan type. The technique is fast, fully automatic, and implemented on commercially available clinical platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Advanced software providing the registration with minimal deformation of image scans and landmarks should be analysed in further studies. Despite some diagnostic limitations, the mpMRI was recommended in several guidelines as staging method as well as method for targeted biopsy in the diagnostic of primary PCa [26][27][28][39][40][41][42][43][44]. In agreement with other studies, both manual and automatic contouring using PSMA-PET techniques showed more accuracy compared to mpMRI for localizing IPLs when correlated with reference biopsy results [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 60%
“…Advanced software providing the registration with minimal deformation of image scans and landmarks should be analysed in further studies. Despite some diagnostic limitations, the mpMRI was recommended in several guidelines as staging method as well as method for targeted biopsy in the diagnostic of primary PCa [26][27][28][39][40][41][42][43][44]. In agreement with other studies, both manual and automatic contouring using PSMA-PET techniques showed more accuracy compared to mpMRI for localizing IPLs when correlated with reference biopsy results [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 60%
“…To our knowledge, two studies have evaluated the inter-reader variability of the zonal anatomy [ 16 , 21 ]; Becker et al [ 16 ] found in a multi-reader study (2 experts radiologists, 2 residents, and 2 computer vision scientists), in a cohort of 80 patients using a 3.0 T MRI and endo-rectal coil, a DSC of 0.733 for the WG and a higher variability for the TZ (DSC 0.738), in the apex (2D DSC 0.85) and basal part of the gland (2D DSC 0.87). Padgett et al [ 22 ] in a multi-reader study ( n = 2) of zonal segmentation on 2D T2W images obtained on 3 T of 30 consecutive patients found for the WG a DSC of 0.88 ± 0.04 and 0.81 ± 0.1 for the TZ.…”
Section: Discussionmentioning
confidence: 99%
“…T2 harmonization between different scanners is a recognized challenge using the T2W sequence and this is emphasized, particularly when conducting multicenter studies. 24,30 As with our previous work, 36,41 the proposed normalization was developed and tested in a very heterogeneous dataset (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%